The effect of health education on knowledge of pregnant women about the danger signs of third-trimester pregnancy at IMP Nursyamsiah, SST in 2022 - Siti Rohani; Rini Wahyuni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
One of the things that influence knowledge is education. With the educational process, it is hoped that there will be changes in knowledge, attitudes, and skills. The purpose of this study was to determine the effect of health education on the level of knowledge of pregnant women about the danger signs of third-trimester pregnancy at the Nursyamsiah, S.ST Independent Midwifery Practice (IMP). This research was conducted because many pregnant women still do not know about the danger signs of third-trimester pregnancy, namely as much as 51%. The design used in this research was quantitative with a pre-experimental design, using one group pretest-posttest design approach without a control group. The technique used was an accidental sampling technique. It utilized 28 third-trimester pregnant women as the sample. The data analysis used was univariate and bivariate using the Wilcoxon test. The results of this study were an increase in knowledge about the danger signs of pregnancy in the third trimester from the poor category by 13 respondents (47%). After being given health education, there was an increase where almost all knowledge of third-trimester pregnant women was in a good category by 22 respondents (79%) and sufficient knowledge of as many as 6 respondents (21%). The results of bivariate analysis using the Wilcoxon test obtained a p-value = 0.000 where the p-value was less than 0.05 so that it can be concluded that statistically, health education about the dangerous signs of pregnancy affects increasing the knowledge of third-trimester pregnant women at IMPNursyamsiah., SST. This study’s findings indicate an improvement in third-trimester pregnancy danger signs knowledge from before to after receiving health education. Pregnant women are advised to attend classes specifically for them, and healthcare providers should take a more active role in spreading awareness of health issues. Abstrak: Salah satu yang berpengaruh pada pengetahuan adalah pendidikan. Adanya proses pendidikan diharapkan akan terjadi perubahan pengetahuan, sikap dan keterampilan. Tujuan penelitian ini untuk mengetahui pengaruh pendidikan kesehatan terhadap tingkat pengetahuan ibu hamil tentang tanda bahaya kehamilan trimester III di Praktik Mandiri Bidan (PMB) Nursyamsiah SST. Penelitian ini dilakukan karena masih banyak ibu hamil yang belum mengetahui tentang tanda bahaya kehamilan trimester III yaitu sebanyak 51%. Desain yang digunakan dalam penelitian ini adalah kuantitatif dengan desain Pra Eksperimental, menggunakan pendekatan one group pre test - post test design  tanpa kelompok kontrol. Sampel yang digunakan sebanyak 28 orang ibu hamil trimester III, menggunakan teknik accidental sampling. Analisis data yang digunakan yaitu univariat dan bivariat yang menggunakan uji Wilcoxon. Hasil penelitian ini adanya peningkatan pengetahuan tentang tandabahaya kehamilan trimester III dari kategori kurang sebanyak 13 responden (47%), dan setelah diberikan pendidikan kesehatan terjadi peningkatan dimana hamper seluruh pengetahuan ibu hamil trimester III kategori baik sebanyak 22 responden (79%) dan pengetahuan cukup sebanyak 6 responden (21%). Hasil analisis bivariat menggunakan uji Wilcoxon didapat nilai p value = 0,000 dimana nilai p value kurang dari 0,05 sehingga dapat disimpulkan bahwa secara statistic pendidikan kesehatan tentang tanda bahaya kehamilan berpengaruh terhadap peningkatan pengetahuan ibu hamil trimester III di PMB Nursyamsiah.,SST. Kesimpulan dari penelitian ini yaitu ada peningkatan pengetahuan tentang tanda bahaya kehamilan trimester III dari sebelum ke sesudah diberikan pendidikan kesehatan. Saran untuk ibu hamil diharapkan agar selalu mengikuti kelas ibu.